2020
DOI: 10.1093/ejcts/ezaa195
|View full text |Cite
|
Sign up to set email alerts
|

The results of an entry-oriented strategy for acute type A aortic dissection in octogenarians: an 18-year experience

Abstract: OBJECTIVES The aim of this study was to evaluate the 18-year results of emergency operations for acute type A aortic dissection, especially in octogenarians. METHODS We reviewed 199 patients who underwent surgical aortic repair of an acute type A aortic dissection from January 2001 to December 2018. If the primary entry existed in the ascending aorta, we limited the extent of the replacement to within the ascending aorta. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Data regarding the surgical outcomes in octogenarians were limited and the results were conflicting. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In this study, we reported an improved surgical outcome by using a standard conservative approach of right subclavian artery cannulation, no aortic cross-clamp, selective antegrade cerebral perfusion, moderate systemic hypothermia, reinforced sandwich technique, and a strategy of limited aortic resection. The majority of operative survivors were discharged alive and well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data regarding the surgical outcomes in octogenarians were limited and the results were conflicting. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In this study, we reported an improved surgical outcome by using a standard conservative approach of right subclavian artery cannulation, no aortic cross-clamp, selective antegrade cerebral perfusion, moderate systemic hypothermia, reinforced sandwich technique, and a strategy of limited aortic resection. The majority of operative survivors were discharged alive and well.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing experience and improving surgical techniques in AAAD surgery, the operative mortality rate among octogenarians has declined to less than 30%, especially in experienced centers. [12][13][14][15][16][17][18][19][20][21] However, a significant number of the operative survivors had compromised quality of life. Hata et al 12 have reported that 17% of operative survivors were bedridden and 46% were demented.…”
Section: Aaad Surgery In Octogenariansmentioning
confidence: 99%
See 1 more Smart Citation
“…Igarashi et al reported that in 199 patients and 25 octogenarians with ATAAD, multivariate logistic regression analysis identified chronic kidney disease as a significant factor for hospital mortality ( p = 0.006; odds ratio, 10.93; 95% CI, 1.996–59.846). 10 Maisat et al 16 reported that prolonged mechanical ventilation was significantly associated with increased hospital mortality and increased ICU and hospital low-output syndrome. In a large Japanese study, Ohnuma et al 17 analyzed the Japanese Diagnosis Procedure Combination database, a Japanese case-mix classification system linked with a payment system.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is evidence of temporally improving surgical outcomes of ATAAD repair in recent decades, [1][2][3] short-term mortality in surgical patients remains substantial at approximately 15% to 30%. [3][4][5][6][7][8][9][10][11][12][13] In addition to hemodynamic compromise, degree of malperfusion, and burden of comorbidities, age has been consistently identified as a risk factor for intra-and postoperative mortality for patients undergoing surgical repair for ATAAD. 1,2,6,9,11,12,[14][15][16][17][18][19][20][21][22][23][24][25] Given the aging population of the United States and the rising prevalence of thoracic aortic disease in older patients, 24,26 it is becoming increasingly important to understand contemporary outcomes in this patient population.…”
Section: See Commentary On Page XXXmentioning
confidence: 99%